Reimagining Education in the Post-COVID-19 Era: Embracing Technology, Promoting Resilience, and Fostering Equity - Ani Nafisah; Cittra Juniarni; Almujahid Almujahid; Hesta Rafmana; Mona Novita (Penelitian dan Pengembangan Ilmu, 2024)
This research aims to explore the effectiveness of distance learning (PJJ) strategies in overcoming the digital divide and promoting educational equality in rural areas post-COVID-19 pandemic. Using a systematic literature review approach, this study analyzes various relevant literature, including peer-reviewed articles, research reports, and case studies. The findings show that although PJJ can improve access to education, significant challenges related to digital infrastructure, technology skills, and inclusive education policies still need to be addressed. This research emphasizes the importance of investing in digital infrastructure, training for educators and students, and developing fair policies to support the success of PJJ in rural areas. The results of this research make a significant contribution to the existing literature and offer valuable insights for policy makers, educators, and school administrators in creating equitable learning environments.